Metagenomic insights into microbial community dynamics of fermented Indigofera zollingeriana supplemented with probiotics and phytobiotics - IRWAN SUSANTO; ANURAGA JAYANEGARA; RONI RIDWAN; I KOMANG G. WIRYAWAN; ERIKA B. LACONI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Susanto I, Jayanegara A, Ridwan R, Wiryawan IKG, Laconi EB. 2025. Metagenomic insights into microbial community dynamics of fermented Indigofera zollingeriana supplemented with probiotics and phytobiotics. Biodiversitas 26: 2684-2695. Silage fermentation is an effective method for preserving forage by utilizing microbial activity under anaerobic conditions to maintain its nutritional value and prolong storage stability. Indigofera zollingeriana is a high-protein and fibre-rich forage, making it a promising candidate for silage. However, fermentation success depends on microbial communities involved in organic matter degradation. This study employed Next-Generation Sequencing (NGS) with the Illumina platform to analyze the microbial composition of Indigofera silage, enabling precise genus-level identification via 16S rRNA sequencing. The study evaluated microbial diversity and population shifts in silage supplemented with phytobiotics, probiotics, and their combination. The results showed that Gammaproteobacteria dominated all treatments (>90%), with Bacilli and Alphaproteobacteria present in smaller proportions. The combination treatment exhibited the highest microbial diversity, with increased Betaproteobacteria and Actinomycetes, which aid fibre degradation. The low presence of Clostridia suggested well-controlled fermentation. At the family level, Enterobacteriaceae were dominant in single LAB and phytobiotic treatments, while the combination treatment reduced Enterobacteriaceae and increased Moraxellaceae and Enterococcaceae, which support fermentation stability. At the genus level, Enterobacter was prevalent, but the combination treatment increased Pantoea and Leclercia, indicating a more balanced fermentation ecosystem. Alpha diversity and Principal Coordinates Analysis (PCoA) confirmed that the combination treatment promoted microbial diversity and fermentation stability while suppressing Enterobacter cloacae. Treatment using acacia bark extract showed effectiveness in the smallest Costridia population (2%). These findings highlight the importance of combining probiotics and phytobiotics to enhance silage quality and microbial balance, emphasizing the need for further research on microbial interactions in fermentation.